TANGGAP PERTUMBUHAN DAN PRODUKSI JAGUNG PIONEER 23 TERHADAP BERBAGAI KOMPOSISI VERMIKOMPOS DAN PUPUK ANORGANIK - Efrida Sari Nasution; Mariati Mariati; Asil Barus (Universitas Sumatera Utara, 2012)
ABSTRACT Growth and yield response of maize Pioneer 23 on the several compotitions of vermicompost and inorganic fertilizers. Maize is a staple food after rice and has significant impact on the development of industry in Indonesia. Increased maize production is accompanied by the use of inorganic fertilizer. The application of inorganic fertilizer continuously without the use of organic matter results in land degradation. A solution to solve this problem is to use vermicompost which is basically the conversion of organic material by earthworms. The research was conducted to investigate response of the growth and yield of maize Pioneer 23 variety to several compotitions of vermicompost and inorganic fertilizers, using Non factorial Randomized Block Design with 11 treatments, which were P0 (control); P1 (vermicompost 2,5 kg/plot); P2 (N, P, K fertilizer 100 %); P3 (vermicompost 2,5 kg/plot + N, P, K fertilizer 100 %); P4 (vermicompost 2,5 kg/plot + N, P, K fertilizer 75 %); P5 (vermicompost 2,5 kg/plot + N, P, K fertilizer 50 %); P6 (vermicompost 2,5 kg/plot + N, P, K fertilizer 25 %); P7 (vermicompost 2 kg/plot + N, P, K fertilizer 100 %); P8 (vermicompost 2 kg/plot + N, P, K fertilizer 75 %); P9 (vermicompost 2 kg/plot + N, P, K fertilizer 50 %); and P10 (vermicompost 2 kg/plot + N, P, K fertilizer 25 %).The results showed that the several compotitions of vermicompost and inorganic fertilizers had no significant effects on all parameters, except for the plant diameter and 100 grain weight. Key words: Maize, vermicompost, inorganic fertilizer ABSTRAK Tanggap Pertumbuhan dan Produksi Jagung Pioneer 23 Terhadap Berbagai Komposisi Vermikompos dan Pupuk Anorganik. Jagung merupakan bahan makanan pokok setelah beras dan mempunyai arti penting dalam pengembangan industri di Indonesia. Peningkatan produksi jagung selalu diiringi dengan penggunaan pupuk anorganik. Penggunaan pupuk anorganik secara terus menerus tanpa diimbangi dengan bahan organik mengakibatkan terjadinya degradasi lahan. Solusi yang dapat dilakukan untuk mengatasi masalah ini adalah menggunakan vermikompos dimana vermikompos pada dasarnya merupakan hasil perombakan bahan organik oleh cacing tanah. Penelitian ini dilakukan untuk meneliti pertumbuhan dan produksi jagung varietas Pioneer 23 terhadap berbagai komposisi vermikompos dan pupuk anorganik, yang menggunakan Rancangan Acak Kelompok Non Faktorial dengan 11 perlakuan yang mana P0 (kontrol); P1 (vermikompos 2,5 kg/plot); P2 (pupuk N, P, K 100 %); P3 (vermikompos 2,5 kg/plot + pupuk N, P, K 100 %); P4 (vermikompos 2,5 kg/plot + pupuk N, P, K 75 %); P5 (vermikompos 2,5 kg/plot + pupuk N, P, K 50 %); P6 (vermikompos 2,5 kg/plot + pupuk N, P, K 25 %); P7 (vermikompos 2 kg/plot + pupuk N, P, K 100 %); P8 (vermikompos 2 kg/plot + pupuk N, P, K 75 %); P9 (vermikompos 2 kg/plot + pupuk N, P, K 50 %); dan P10 (vermikompos 2 kg/plot + pupuk N, P, K 25 %). Hasil penelitian menunjukkan bahwa berbagai komposisi vermikompos dan pupuk anorganik berpengaruh tidak nyata dengan semua parameter, kecuali diameter batang dan bobot 100 biji. Kata kunci: Jagung, vermikompos, pupuk anorganik